2014
DOI: 10.4103/2141-9248.141525
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammatory cytokines with traditional and nontraditional cardiovascular risk factors in Indians with known coronary artery disease

Abstract: Background:Inflammatory processes are implicated in the etiology of cardiovascular disease (CVD). Data on the association of inflammatory markers with cardiovascular risk factors in Indian patients with CVD are limited.Aim:This study was conducted with the aim to evaluate the association of inflammatory markers with traditional and nontraditional cardiovascular risk factors in angiographically proven coronary artery disease (CAD) patients.Subjects and Methods:We studied the association of serum highly sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Previous researchers have reported that CAD is a chronic inflammatory process, suggesting that inflammatory cytokines play a major role in the progression of CAD [2,3]. Interleukin-6 (IL-6), as a pleiotropic cytokine of 23.7 kDa, is one of the important inflammatory cytokines and regulates the inflammatory response of CAD [4,5]. The human IL-6 gene is situated in chromosome 7p21 and there are three single nucleotide polymorphisms (SNPs) at the 50 flanking region of the IL-6 gene promoter [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have reported that CAD is a chronic inflammatory process, suggesting that inflammatory cytokines play a major role in the progression of CAD [2,3]. Interleukin-6 (IL-6), as a pleiotropic cytokine of 23.7 kDa, is one of the important inflammatory cytokines and regulates the inflammatory response of CAD [4,5]. The human IL-6 gene is situated in chromosome 7p21 and there are three single nucleotide polymorphisms (SNPs) at the 50 flanking region of the IL-6 gene promoter [6].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Various research studies were carried out on CAD patients in Indian population for the assessment of inflammatory status. The association of inflammatory markers like IL-6, TNF alpha, 10 homocysteine, 11 ferritin, 12 Lp (a) 13 and hsCRP 14 with CAD has been shown in Indians. hsCRP has been identified as one of the promising one.…”
Section: Introductionmentioning
confidence: 99%
“…9 Increased level of interleukin-6 was seen in acute myocardial infarction, coronary syndrome, unstable angina patients, acute and in advanced heart failure patients. 4,5,[9][10][11][12][13][14][15][16][17][18] Until now C reactive protein is the only established inflammatory marker by World Health Organization standard for coronary risk. 19 Therefore, authors hypothesized that this interleukin-6 can not only serve as new marker for diagnosis of heart failure but also can be used for identification of high risk heart failure patients.…”
Section: Introductionmentioning
confidence: 99%